Analisis Efektivitas Program Raskin dan Ketahanan Pangan Rumah Tangga Miskin “Kasus Di Propinsi Jawa Barat Tahun 2010” - Alla Asmara; Sri Hartoyo; Rina Oktaviani; Lukytawati Anggraeni (Institut Pertanian Bogor, 2010)
Realizing that there are still alot of poor households (RTM) in Indonesia, the government through various programs and policies continue to improve the food security conditions of poor households, particularly through Raskin. The implementation of Raskinhas been running about ten years. However, the criteria of “Enam Tepat” as indicator of success oof Raskin, has not been fully achieved. The purpose of this study consist of: Firstly, analyze the effectiveness of the Raskin program in West Java. Secondly, analyze the condition of the food security of poor households in West Java. The study was designed as a research survey with the simple random sampling method.The results showed that the actual Raskin recipients exceed the amount of targeted households (RTS) with deviations ranging from 17.33 to 164.23 percent. Deviation in the quantity indicator ranged from 14.77 to 62.15 per cent. While, the price deviations ranged from 14.26 to 40.19 per cent. For timely indicators of Raskinis generally achieved. Analysis on food security conditions of poor households showthat the poor households that categorized as vulnerable on food is approximately 6.7 percent to 34.5 percent.